THE CORRELATION OF FAMILY SOCIO-ECONOMIC, MAINTENANCE OF DENTAL HEALTH, AND PHYSICAL ENVIRONMENT FACTORS WITH DENTAL AND ORAL HEALTH - Aspiani Aspiani; Rosihan Adhani; Galuh Dwinta Sari (Dentin, 2023)
ABSTRACTBackground: Dental and oral health problems in Indonesia continue to increase. Dental and oral health is part of the overall health of the body. Dental and oral health in adolescents is an essential and integral part of general health seen in the wider community. Junior high school students are teenagers who experience significant development in their lives, both physically, emotionally, socially, and behaviorally.  Purpose: To analyze the correlation of family socio-economic, dental health maintenance, and the physical environment factors with dental and oral health conditions in UPT SMP Negeri 1 Cempa students. Material and Methods: This study used an analytic observational method with a cross sectional research design The sample was determined using the sample size correlation formula. The population were students of UPT SMP Negeri 1 Cempa as many as 414 people and the sample used was 40 respondents. Results: Spearman correlation test to determine the correlation between dental health maintenance and oral health obtained the value of Sig. 0.005 means that there is a correlation between the level of dental health maintenance with dental and oral health conditions (p <0.05). There was no significant correlation between the socioeconomic level of the family (Sig. 0.167; p>0.05) and the level of physical environmental conditions (Sig. 0.710; p>0.05) with dental and oral health condition. Conclusion: There is a significant correlation between the level of dental health maintenance and dental and oral health conditions, while the socioeconomic level of the family and the physical environment does not have a correlation with dental and oral health conditions.Keywords: Dental and oral health, Dental health maintenance, Physical environment, Socioeconomic.